Multiple objective optimization for systems with addition–min fuzzy relational inequalities - Guu, Sy-Ming; Wu, Yan-Kuen (Fuzzy optimization and decision making, 2019)
Fuzzy relational inequalities with addition–min composition have been proposed to model the data transmission mechanism in a BitTorrent-like peer-to-peer file-sharing system. In this paper, we consider a multiple objective optimization problem which allows system manager to consider three objectives (system congestion, cost, and penalty) simultaneously. A quadratic program is then proposed for finding its efficient solutions. Numerical examples are given to illustrate the procedures of the quadratic programming approach.